Seismic vulnerability assessment, damage scenarios and loss estimation: case study of the old city centre of Coimbra, Portugal - Vicente, R. (2012)
The evaluation of the seismic risk of built-up areas is associated to the level of earthquake hazard, building vulnerability and level of exposure. Within this holistic approach that defines seismic risk, building vulnerability is from all three variables, the one that assumes great importance not only because of its obvious physical consequences in the occurrence of a seismic event, but because it is the potential aspect, for which the engineering research can intervene, improve and even control seismic behaviour of existing buildings, reducing the level of vulnerability and consequently the level of physical damage, life loss and economical loss. Development of vulnerability studies in urban centres can be conducted aiming to identify building fragilities and reduce the seismic risk, therefore in the scope of the rehabilitation process of the old city centre of Coimbra, a complete identification and inspection survey of the old masonry buildings has been carried out. The main purpose of this paper is to discuss the vulnerability assessment methodologies, particularly the first level approaches, by presenting a proposed method which determines previously the level of vulnerability, only then assessing physical damage and its relationship to seismic intensity. It is presented and discussed the strategy and proposed methodology adopted for the vulnerability assessment, damage and loss scenarios for the city centre of Coimbra, in Portugal, through the GIS mapping of the building stock of the project perimeter.